Designing financial instruments for land-based ecological restoration: A review and future research Agenda - John Garvey; Vasilis Grigoriadis; Darragh Flannery; Edward Knapp; Elizabeth Gold; George Hutchinson; Lynn J. Frewer; Paul Brereton; Kenneth A. Byrne (Cleaner Production Letters)
Land restoration requires innovative approaches to prevent ongoing degradation and increase the functionality of land use. While land restoration has been studied extensively from the perspective of ecologists and local communities it is a topic that remains at the periphery of the financial economics literature, despite the global financial system’s centrality to the problem. This paper reviews the literature on financial instruments that are designed for land-based ecological restoration, extracts key learnings from this literature and deploys a functional perspective to better understand how financial instruments that aim to scale up land restoration activities can be mainstreamed within the global financial system. This paper presents a framework that promotes public channels to best direct public and private capital towards land restoration projects. Matching the supply of capital with a pipeline of spatially explicit and sometimes unique restoration solutions requires an architecture that can implement this coordination and aggregation function. This has the potential to mitigate transaction costs and improve transparency issues associated with monitoring and reporting. This framework is illustrated for an actual land restoration program underway in Europe.